Vegetative and productive performance of plantain genotypes of the Terra subgroup - Nomura, Edson Shigueaki; Junior, Erval Rafael Damatto; Rodriguez, Miguel Angel Dita; Amorim, Edson Perito; Drominiski, Alex Mesczezem [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the vegetative and productive performance of plantain (Musa spp.) genotypes of the Terra subgroup under the environmental conditions of the Ribeira Valley in the state of São Paulo, Brazil. The experimental design was randomized complete blocks, with 12 genotypes and four replicates. Two types of genotypes were evaluated: six of the French plantain type, using the Maranhão cultivar as a reference; and six of the Horn plantain type, using the D’Angola cultivar as a reference. The treatments were evaluated during two production cycles, based on the following variables: pseudostem height and diameter, number of active leaves, total number of suckers and of plant cycles, fruit fresh mass, fruit length and diameter, fresh mass of the second hand, number of hands and of fruits in the bunch, bunch mass of marketable fruits, and productivity. Of the Horn plantain genotypes, 78 and 88 presented a better vegetative and productive performance, smaller plants, a larger pseudostem diameter, and a higher productivity than the D’Angola cultivar. None of the French plantain genotypes was superior to the Maranhão cultivar in terms of productivity and fruit quality. However, genotypes 79, 80, 82, and 84 present, as differential characteristics, a lower pseudostem height and a shorter total cycle, which could be explored to improve their productive potential.
Desempenho vegetativo e produtivo de genótipos de bananeira do subgrupo Terra
Keywords: agronomic performance; banana de cozinhar; cooking banana; desempenho agronômico; Musa; plantain; plátanos